2012
DOI: 10.1002/jmri.23825
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐system repeatability and reproducibility of apparent diffusion coefficient measurement using an ice‐water phantom

Abstract: Purpose Quantitative quality control procedures were sought to evaluate technical variability in multi-center measurements of the diffusion coefficient of water as a prerequisite to use of the biomarker apparent diffusion coefficient (ADC) in multi-center clinical trials. Materials and Methods A uniform data acquisition protocol was developed and shared with 18 participating test sites along with a temperature-controlled diffusion phantom delivered to each site. Usable diffusion weighted imaging data of ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
215
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(239 citation statements)
references
References 22 publications
(6 reference statements)
22
215
2
Order By: Relevance
“…1) in the ice-water phantom at four repeat scans were 1.113, 1.112, 1.113, and 1.112 · 10 -3 mm 2 /s, respectively. These ADC values were consistent with the literature (33,34), showing that the ADC measurement was highly reproducible in DW-MRI. In another study with healthy volunteers, the ADC values of thyroid gland from 9 volunteers across the exams were 1.84 -0.33 vs 1.74 -0.27 vs 1.74 - 2 /s (0.77 -0.14); p < 0.01 ( p < 0.001)].…”
Section: Resultssupporting
confidence: 91%
“…1) in the ice-water phantom at four repeat scans were 1.113, 1.112, 1.113, and 1.112 · 10 -3 mm 2 /s, respectively. These ADC values were consistent with the literature (33,34), showing that the ADC measurement was highly reproducible in DW-MRI. In another study with healthy volunteers, the ADC values of thyroid gland from 9 volunteers across the exams were 1.84 -0.33 vs 1.74 -0.27 vs 1.74 - 2 /s (0.77 -0.14); p < 0.01 ( p < 0.001)].…”
Section: Resultssupporting
confidence: 91%
“…Future studies are required to investigate this issue, as a high robustness is a prerequisite for the use of DWI in treatment monitoring. A recently published study using an ice water phantom has demonstrated that DWI data acquisition using a DWI protocol designed for comparability across scanners might compensate differences in scanner geometry leading to a high robustness of ADC measurements [40]. However, based on our data, studies on the combined use of ADC and SUV values derived from PET/MRI for the prediction of therapy response are rewarded.…”
mentioning
confidence: 81%
“…The authors reported a ± 5% variation in ADC across all systems and singlesystem repeatability was also ± 5%. Malyarenko et al [137] (2013) reported a multi-centre study using a variation of the ice-water phantom developed by Chenevert et al [125] . The authors devised a DW-MRI protocol compatible across 35 clinical MRI platforms (GE, Philips, Siemens) at 18 institutions at two field strengths of 1.5T and 3.0T.…”
Section: Reproducibility Of Adc Values In Vitromentioning
confidence: 99%